Language of Administration as a Border: Wild Food Plants Used by Setos and Russians in Pechorsky District of Pskov Oblast, NW Russia - Olga Belichenko; Valeria Kolosova; Denis Melnikov; Raivo Kalle; Renata Sõukand (Foods, 2021)
Socio-economic changes impact local ethnobotanical knowledge as much as the ecological ones. During an ethnobotanical field study in 2018–2019, we interviewed 25 Setos and 38 Russians in the Pechorsky District of Pskov Oblast to document changes in wild plant use within the last 70 years according to the current and remembered practices. Of the 71 botanical taxa reported, the most popular were Vaccinium vitis-idaea, Vaccinium oxycoccos, Vaccinium myrtillus, Betula spp., and Rumex acetosa. The obtained data was compared with that of 37 Setos and 35 Estonians interviewed at the same time on the other side of the border. Our data revealed a substantial level of homogeneity within the plants used by three or more people with 30 of 56 plants overlapping across all four groups. However, Seto groups are ethnobotanically closer to the dominant ethnic groups immediately surrounding them than they are to Setos across the border. Further study of minor ethnic groups in a post-Soviet context is needed, paying attention to knowledge transmission patterns.